2011
DOI: 10.1590/s1677-04202011000400005
|View full text |Cite
|
Sign up to set email alerts
|

Thinning with NAA, NAD, ethephon, urea and by hand to improve fruit quality of 'Gerdi' apricot

Abstract: This research was conducted to study the effects of chemical and hand thinning on fruit quality of 'Gerdi' apricot. In the first year, three weeks after full bloom (AFB) branches of mature trees were sprayed with naphthalene acetic acid (NAA) at 10, 20, and 40 mg L , and NAD at 40 and 80 mg L -1 increased fruit weight in 2006, but only the highest concentration of NAD was effective in 2007, while urea was effective at all concentrations in both years. Ethephon effect on fruit weight was not significant at all.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 14 publications
2
7
1
Order By: Relevance
“…However, GA3 (100, 125)mg.l -1 in combination with NAA (50,100) mg.l -1 gave maximum value of oil of olive trees cv. The obtained results are in parallel with Taghipour et al (2011) who found that the treatment (acid boric at 100 mg/l and Urea at 500 mg/l) resulted in the highest oil content of olive.…”
Section: Effect Of Thinning Agents On Oil Content Of Manzanillo and Esupporting
confidence: 87%
See 2 more Smart Citations
“…However, GA3 (100, 125)mg.l -1 in combination with NAA (50,100) mg.l -1 gave maximum value of oil of olive trees cv. The obtained results are in parallel with Taghipour et al (2011) who found that the treatment (acid boric at 100 mg/l and Urea at 500 mg/l) resulted in the highest oil content of olive.…”
Section: Effect Of Thinning Agents On Oil Content Of Manzanillo and Esupporting
confidence: 87%
“…applied on the earliest of the dates selected (8 and 12) days after full bloom increased fruit weight by reducing crop density and enhancing the leaf to fruit ratio, without reducing yield. Taghipour et al (2011) found that NAA at 20 and 40 mg L -1 increased fruit weight, while Urea was effective at all concentrations in both years.…”
Section: Effect Of Thinning Agents On Fruit Weight (G) Of Manzanillo mentioning
confidence: 84%
See 1 more Smart Citation
“…Nevertheless, other than the genetic factors, there are many other factors that might increase the fruit weight such as pruning, thinning, increased irrigation, fruit water accumulation during the enlargement of mesocarp cells, nitrogen, urea, macromineral availability (e.g., especially of K and P, but also of Ca and Mg), and phytohormones (e.g., gibberellic acid or gibberellin) [29][30][31][32][33][34][35][36][37][38][39][40][41][42]. Some of these factors are obviously interrelated, but many may also be confounding.…”
Section: Cubiu Fruit Weight During Ripeningmentioning
confidence: 99%
“…Unfruitfulness in olive has frequently been observed which may be attributed to numerous factors. Some of them are probably related to the internal imbalance of growth regulators and other physiological factors (Taghipour et al, 2011 andBirger et al, 2008). Biennial bearing is a major horticultural and economical drawback of olive cultivation, which particularly affects the olive oil industry (Dag et al, 2009).…”
Section: Introductionmentioning
confidence: 99%